Algebraic groups and number theory, Volume I - Platonov, Vladimir P. 1939-; Rapinčuk, Andrej S. 1960-; Rapinchuk, Igor (Cambridge studies in advanced mathematics, 2023)
This is the first volume of a two-volume book that offers an in-depth, and essentially self-contained, treatment of the arithmetic theory of algebraic groups. It is accessible to graduate students and researchers in number theory, algebraic geometry, and related areas.